Online Radicalism, When Online Surfing Leads to Suffering - Imam Malik; Khoirul Anam; Sukron Ma’mun (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
The development of online media has long played big roles in the spreading of intolerance and radicalism, in some levels, the online media is also used as a media to spread propaganda and to conduct online recruitment. Data compiled by Gabriel Weimann shows that radical groups use online media seriously to spread their wings in influencing and asking people to joint their movement. In 1998, radical-terrorist groups only had 12 sites, while in 2003 they had 2.650 sites. The number increased so high in 2014 where these groups are known to have more than 9.800 sites. The shifting place, from offline to online, used by radical groups to conduct their activities impacts to the targets they aim; online radicalism targets youth to become ‘jihadis’. A national survey conducted by Wahid Foundation on potency of intolerance and radicalism in Rohis (an after-school program focused on Islamic spirituality) shows this fact; 33% Rohis put terrorist suspect like Amrozi, Imam Samudra, Abu Bakar Ba’asyir, and Bahrun Na’im as the living example of Muslim practicing the real jihad. 37% believes that Osama bin Laden died syahid, 6% of them even support international terrorist group, ISIS. The article is designed to analyze how radical groups use online media to radicalize youth, as well as supporting factors surrounding the live of youth, especially in big cities of Indonesia.